Kunci melawan kekerasan seksual di kampus: Memahami faktor, dampak, dan solusi - Budianto, Putri (Maliki Interdisciplinary Journal, 2024)
Sexual violence on campus is a complex problem influenced by various factors, such as lack of sex education, abuse of power, and opportunities exploited by perpetrators. Many students do not understand the importance of sex education as protection against sexual violence. Abuse of power by lecturers or student organization leaders exacerbates the problem, where perpetrators exploit their positions to harm victims. Situations such as exams, consultations, or organizational meetings also open up opportunities for harassment. The impact of sexual violence is very broad, including physical, psychological, social, and academic disorders that harm victims in the long term. To overcome this problem, sex education needs to be integrated into the university curriculum so that students understand their rights and boundaries in relationships. In addition, awareness campaigns and clear policies related to handling cases of sexual violence are essential. Gender equality and prevention of sexual violence must also be strengthened through student organizations, in order to create a safe and inclusive campus environment.